DETERMINAN FINANCIAL DISTRESS, THIN CAPITALIZATION, KARAKTERISTIK EKSEKUTIF, DAN MULTINATIONALITY TERHADAP PRAKTIK TAX AVOIDANCE PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Curry, Khirstina; Fikri, Imam Zul (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
The rise of tax avoidance today is one of the foundations of research carried out. Many tax avoidance schemes are carried out by enterprises.The practice of tax avoidance is an act of tax avoidance that takes advantage of loopholes in the tax law. For this reason, this study aims to estimate and analyze how the influence of financial distress, thin capitalization, executive characteristics and multinationality on tax avoidance practices during the 2015 - 2020 period. Using the Panel data method on companies that are included in the property and real estate sub-sector, shows the results that financial distress and thin capitalization have a negative effect on the practice of tax avoidance. It is different with executive characteristics and multinationality which do not affect the practice of tax avoidance. The use of debt is also one of the alternatives that can be done in tax planning such as the practice of tax avoidance. But it is worth noting that large debts do not always guarantee that the company will be able to run stably. There is a high probability that debt if it is not accompanied by the ability to fulfill obligations will result in tax planning not running well.